Quiste óseo traumático: técnicas diagnósticas - Watanabe, Plauto; Assad-Nader, Habib; López-Labadessa, Luiz Mario (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The Traumatic Bone Cyst is a cavity at the mandible that isn’t cepped by epithelial tissue, several times is considered a false cyst. The objective of the authors is report a clinic case, supervisioned byan excelent anamnese and with a convencional radiografic exsminetion, had diagnose the lesion how being probably Traumatic Bone Cyst. who oriented all the casepresentation. The lesion had a regression and estabilization.